UNPACKING THE CYCLE OF SOCIAL MEDIA ADDICTION: UNDERSTANDING SYMPTOMS, PROGRESSION, AND RECOVERY - Omar, Zakaria Saleh (Journal of Current Research and Review (JCRR), 2022)
Social Media is beneficial when used properly. It's useful for keeping in touch with far distance friends, hard to meet friends and longtime friends, and knowing what they're doing recently, and how thing is going with them. Every social media outlet has their own purpose, and it is clear how powerful social media is in this digital age, so when it is used wrongly, then the benefit will be over shadowed by these disadvantages. Misuse of social media can lead to many consequences, like loss of privacy, ‗cyber-bullying‘, time consumption, loss of traditional social skills. This research is intended to provide practical and theoretical insight into the developing circumstance observed about social media addiction by summarizing social media usage patterns, and the personalities of social media users, identifying the consequences of abusing social media usage, and identifying the signs for potential social media addiction. The outcome of this research should help social media users figure out if the social media is helping or ruining their lives. This research is done in cooperation between information systems specialists and a mental health care professional, trained in dealing with addictions. The findings of this research point out the major indicators for the individual's level of use in each of the expected stages that can lead to the social media addiction, and recommends the practical countermeasures that should be taken to avoid the potential addiction. This research refers to the individuals who responded to the survey as respondents, and the interviewed ones in a clinical setting as participants.